Natural hazard mapping across the world. A comparative study between a social approach and an economic approach to vulnerability - Gilles André (Cybergeo)
Over the last twenty years, natural disasters have occupied an important place in our minds and in the media. These disasters have been considered in the past as the manifestation of divine anger or fate, but scientific progress has brought a rationalization in ways of thinking, making us less tolerant towards them. While many studies have focused on the characterisation of the physical processes that lead to these phenomena, few studies have sought to produce a global estimation of the exposure of the different countries across the world to natural hazards, exploring different approaches to vulnerability. The aim of our paper is to present a comparative study of risk exposure for each country, combining two approaches to their vulnerability (social and economic), and a probabilistic approach to hazards. This work highlights the fact that, using a social approach to vulnerability, great inequalities are observed between “rich” countries and “poor” countries where the latter present higher levels of exposure to risk, while using an economic approach to vulnerability, “rich” countries present the highest levels of exposure to risk. Keywords: map, natural hazard, vulnerability, hazard, inequality